Applying, C2→C2 + C1
Taking, (a + b + c) common,
Applying R2→R2 – R1, and R3→R3 – R1
Taking, (b – c) and (c – a) common,
= (a + b + c)(b – a)(c – a)(b – c)
So, Δ = (a + b + c)(b – a)(c – a)(b – c)
Rate this question :
How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
view all courses
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation